Adult coronary artery bypass grafting by congenital surgeons—a propensity matched analysis. (15th February 2021) - Rapetto, Filippo; Bruno, Vito D; Rajakaruna, Cha; Bryan, Alan J; Parry, Andrew J; Caputo, Massimo; Stoica, Serban C
Abstract: : OBJECTIVES: Surgical myocardial revascularization will be increasingly needed in adult patients with congenital heart disease. We investigated the results of coronary artery bypass grafting (CABG) performed on adults by congenital cardiac surgeons at our institution. METHODS: We conducted a retrospective, single-centre study. Adults undergoing isolated or combined CABG from 2004 to 2017 were included. Early and late outcomes were analyzed for the whole cohort. Furthermore, a propensity matched analysis was conducted comparing the results of isolated CABG between congenital and adult surgeons. RESULTS: A total of 514 and 113 patients had isolated and combined CABG for acquired heart disease, respectively. A total of 33 patients had myocardial revascularization at the time of surgery for congenital heart disease. Overall early mortality was 1.2%, the rate of re-exploration for bleeding was 4.5%, and an internal mammary artery to left anterior descending artery graft was used in 85.6% patients. One-year survival was 97.5% (96.2–98.8%), and 5-year survival was 88.0% (84.8–91.3%). After propensity matching (468 pairs), early mortality (0.6% vs 1.2%, P = 0.51), re-exploration for bleeding (3.6% vs 3.0%, P = 0.72), use of internal mammary artery to left anterior descending artery graft (92.7% vs 91.9%, P = 0.70) and late survival did not differ between congenital surgeons and adult surgeons, respectively. CONCLUSIONS: Surgical myocardial revascularization can be required for adult congenital patients in a broad spectrum of clinical situations. Despite lower volumes, congenital cardiac surgeons perform CABG safely and with results that are comparable to those of the adult surgeons at our centre.